2022
DOI: 10.1002/vms3.912
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐Trypanosoma activities of medicinal plants: A systematic review of the literature

Abstract: Background The existing drug treatments for trypanosomiases are limited and suffer from shortcomings due to their toxicity and the emergence of resistant parasites. Developing anti‐trypanosomal compounds based on natural products is a promising way of fighting trypanosomiases. Objectives This study aims to identify through scientific review a large variety of medicinal plants (anti‐trypanosomal) used worldwide and scientifically shown to display anti‐trypanosomal effects. Methods To collect data, the anti‐tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 118 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…It has been described as the presence of Dracocephalum essential oil as a major constituent with good pharmacological properties (Khamesipour et al, 2022;Mahmood et al, 2005). In addition, numerous studies showed that these oils present important effects acting as antioxidants (Ehsani et al, 2017;Fallah et al, 2018;Sonboli et al, 2012;Zhang et al, 2008), insecticidal (Chu et al, 2011;Özek et al, 2016), phytotoxic (Jalaei et al, 2015;Suleimen et al, 2017), cytotoxic (Sonboli et al, 2012), antinociceptive (Golshani et al, 2004), antispasmodic (Sadraei et al, 2015), antimicrobial (Ehsani et al, 2017;Lee et al, 2007) and antiparasitic (Ghanadian et al, 2021;Khamesipour et al, 2020;Nekoei et al, 2022). D. kotschyi is a wild-growing flowering plant of Dracocephalum species and is commonly found in southwestern Asia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been described as the presence of Dracocephalum essential oil as a major constituent with good pharmacological properties (Khamesipour et al, 2022;Mahmood et al, 2005). In addition, numerous studies showed that these oils present important effects acting as antioxidants (Ehsani et al, 2017;Fallah et al, 2018;Sonboli et al, 2012;Zhang et al, 2008), insecticidal (Chu et al, 2011;Özek et al, 2016), phytotoxic (Jalaei et al, 2015;Suleimen et al, 2017), cytotoxic (Sonboli et al, 2012), antinociceptive (Golshani et al, 2004), antispasmodic (Sadraei et al, 2015), antimicrobial (Ehsani et al, 2017;Lee et al, 2007) and antiparasitic (Ghanadian et al, 2021;Khamesipour et al, 2020;Nekoei et al, 2022). D. kotschyi is a wild-growing flowering plant of Dracocephalum species and is commonly found in southwestern Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic plants have long been used to manage several ailments and for various pharmacological uses. Their medical importance is mainly due to their essential oil fractions (Chelgerdi Dehkordi et al., 2022 ; Rajesh & Howard, 2003 ). Essential oils are natural products abundant in nature and have been considered a potential source of antibacterial and antifungal molecules presenting few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, several medicinal properties have been attributed to it. So this plant is used to treat congestion, stomach aches, headaches, and liver disease [7][8][9]. Dracocephalum kotschyi is a plant usually used in modern medicine to treat many human illnesses and prevent tumor cell proliferation worldwide [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Trypanosomiasis is regarded as a serious public health issue in both humans and animals (Nekoei et al, 2022).…”
Section: Introductionmentioning
confidence: 99%